Studi Perkecambahan Benih Sacha Inchi (Plukenetia volubilis L.) Asal Indonesia: Germination Study of Sacha Inchi Seeds (Plukenetia volubilis L.) from Indonesia - Hamdi, Muhammad Fauzan Farid Al; Haryanto, Darban; Kafiya, Maftuh; Aulia Nanda Azzahra; Osama Bintang; Hanifah Dwi Astuti (Jurnal Hortikultura Indonesia, 2025)
Sacha inchi (Plukenetia volubilis) originates from the Peruvian Amazon forest and can be processed into sacha inchi oil, which has a positive impact on human health. This study aims to determine the percentage of germination, germination speed, and seedling morphology in the germination of sacha inchi seeds. The study was conducted in the experimental field and Plant Breeding and Seed Technology Laboratory of the Agrotechnology Study Program, UPN Veteran Yogyakarta, from July 1 to November 12, 2024. The study consisted of a tetrazolium test and a germination test with sand media. The design used was a Completely Randomized Design with two factors in the form of seed accession (Bogor, Cimahi, and Lampung) and germination period, with three replications (July 1, August 22, and October 5, 2024). The results showed non-viable seeds based on the Tetrazolium test on each accession: Bogor: 6%; Cimahi: 10%; and Lampung: 83.3%. The percentage of germination and germination speed of sacha inchi seeds on average in 3 periods was 7.56% and 0.35% etmal-1, found in Cimahi accessions. The rate of germination and germination speed of Cimahi accessions could be higher by 12% and 0.75% etmal-1 in the first period. The type of sacha inchi germination is the epigeal type: a sprout that lifts the cotyledons. The cotyledons are light green, then lifted and leave their seed coats. Keywords: accession, epigeal, germination percentage, germination speed, tetrazolium test